Due To Sell Off Power Of Legal Documents Are Made In Making Act Commerce Land And Buildings By Notary - Paulus Meldif Dika Pratama; Iwa Mashadi; Gunarto Gunarto (Jurnal Akta, 2018)
The purpose of this study was to analyze the legal consequences of the agreement of power sell off made in the manufacture of an agreement of sale by Notary. Legal theory used in this study, among others: justice theory, the theory of authority and responsibility theory. The approach used in this study is primarily sociological juridical approach. Sociological juridical approach is to identify and conceptualize law as a social institution that is real and functional in a real life system. The results of this study finally provides the answer that the certificate authority to sell off which made the authorizer to the Proxy should still be subject to and required for payment of taxes from the sale of land and / or buildings that have been sold such, it thus obliged Notary socialize at the time the parties face because it is concerned responsibility by agreement authorized to sell he made in the manufacture of an agreement of sale in accordance with the provisions stipulated in the Indonesian Government Regulation No. 36 of 2016 regarding Income Tax on Income From the Transfer of Rights to Land and / or Buildings, And Agreements sale and purchase Land And / Or Building Along with its amendment.Keywords: Certificate Authority To Sell; Agreement Of Sale; Notary.